Fat Migration of Lauric and Non-Lauric Fat Used as Base Filling Centre in Dark Chocolate at Different Storage Temperatures - Abdelbagi Ali, Abdelrahim (2001)
The effects of migration of used filling fats palm kernel stearin (PKS), palm midfraction (PMF) and desiccated coconut (DCN) (66% coconut oil) on the physical and chemical characteristics of dark chocolate at different storage temperatures (18°C, 30°C and 35°C) were studied. Fat migration was stimulated in a system by using layers of cream filling and dark chocolates. Total fat content, trigacylglycerol (TAG), fatty acid composition (F AC), solid fat content (SFC), hardness, melting point (MP), polymorphic structure and bloom formation were determined, each week interval for eight weeks. The chocolate samples stored at 18°C showed post-hardening on storage and no indication of softening within two months of storage. There was no significant change in the melting point of chocolate layers (CB). The X-ray diffraction pattern showed that 13 polymorph dominates in chocolate layers during eight weeks of storage, and the chocolates withstand bloom up to 6 months storage. At 30°C, migration occurred rapidly, giving a maximum effect in term of hardness, solid fat content, polymorphic structure, and the chocolate bloom after several weeks of storage. Complete deterioration occurred in all chocolate stored at 35°C at the first week of storage. Sensory evaluation indicated that DCN imparts a pleasant flavour to the chocolate. Fractionated PKS or PMF and DCN fillings will be useful if chocolate was stored at a relatively low temperature below 20°C. It can be concluded that a thickness of 3 mm of chocolate could be used for coating of PKS, PMF and PKS+DCN fillings at 18°C. However, at least a 6mm thickness of chocolate is required to coat PMF+DCN centre at 18°C storage.